2018
DOI: 10.2967/jnumed.117.206045
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Novel Antidepressants on Cardiac 123I-Metaiodobenzylguanidine Uptake: Experimental Studies on SK-N-SH Cells and Healthy Rabbits

Abstract: 123 I-metaiodobenzylguanidine ( 123 I-MIBG) has independent prognostic value for risk stratification among heart failure patients, but the use of concomitant medication should not affect its quantitative information. We evaluated whether the 4 classes of antidepressants currently most prescribed as first-line treatment for major depressive disorder (MDD) have the potential to alter 123 I-MIBG imaging results. Methods: The inhibition effect of desipramine, escitalopram, venlafaxine, and bupropion on 131 I-MIBG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…1). 125 I-MIBG uptake was measured after a 2-h incubation at the nonsaturating concentrations used in the cytotoxicity assay (#925 kBq/mL) with or without blocking with 10 mM of desipramine (12).…”
Section: Radiopharmacologymentioning
confidence: 99%
“…1). 125 I-MIBG uptake was measured after a 2-h incubation at the nonsaturating concentrations used in the cytotoxicity assay (#925 kBq/mL) with or without blocking with 10 mM of desipramine (12).…”
Section: Radiopharmacologymentioning
confidence: 99%
“…Presumably, this suppression results in more "leftover capacity" for NET to transport MIBG intracellular in the sympathetic end organs. In contrast, a recent in vivo rabbit study found no impact of the SSRI escitalopram on cardiac [ 123 I]MIBG uptake [36]. In the liver, citalopram and paroxetine had diametrically opposed effects on the MIBG accumulation.…”
Section: Discussionmentioning
confidence: 83%
“…These findings were further corroborated by electric field stimulation in isolated perfused rabbit hearts: this approach lead to increased washout rate of 18 F-LMI1195, as it provoques vesicular NE release [ 46 ]. Of note, all of those studies were conducted using rabbit myocardium: similar to the human heart, the contribution of NE clearance to neuronal uptake-1 is also pronounced in rabbits and, therefore, the rabbit heart serves as a suitable platform to mimic human cardiac nerve status [ 48 , 49 ]. However, our research group also recently investigated (vesicle-poor) SK-N-SH cells vs. (vesicle-rich) PC12 cells in combination with 18 F-LMI1195 and we found that stimulants for storage vesicle turnover (reserpine, high potassium chloride) enhanced 18 F-LMI1195 washout from PC12 cells, while radiotracer retention remained stable in SK-N-SH cells [ 50 ].…”
Section: Novel Cardiac Neuronal Pet Imaging Agents: 18 mentioning
confidence: 99%